Do individuals prefer stricter supply chain laws? Empirical evidence from Germany - Daniel Engler; Marvin Gleue; Gunnar Gutsche; Gerrit Hornung; Sophia Möller; Sabrina Schomberg; Andreas Ziegler (Philipps-University Marburg, School of Business and Economics, 2025)
Inspired by the controversial public and political debate in the European Union (EU) about legal initiatives to protect human rights and the environment along supply chains (e.g., the Corporate Sustainability Due Diligence Directive, CSDDD), this paper examines individual preferences for different designs of supply chain laws that are stricter than the current national legislation. Our econometric analysis is based on data from a representative online survey of 507 citizens in Germany that especially included a stated choice experiment. Our estimation results show that individuals in Germany, on average, have a significantly positive preference for stricter supply chain laws compared to the existing national Supply Chain Act. In addition, the majority of the respondents expect positive sustainability impacts of supply chain laws, while there is ambiguity in the perceptions of whether the economic consequences are predominantly negative. With respect to political attitudes, our results show that citizens with a social or ecological political identification have significantly stronger preferences for stricter supply chain laws. However, in contrast to the strong opposition of conservative and liberal parties in Germany to stricter supply chain legislation, individuals with a liberal or conservative political identification do not have significantly different preferences for stricter supply chain laws than their counterparts. Our results therefore suggest that the political blockade of supply chain laws does not correspond to the views of the majority of the population in Germany.
Keywords: K23; K32; K38; Q56; Q58; 330; Supply chain laws; individual preferences; stated choice experiment